Characterization of β-Glucans from Cereal and Microbial Sources and Their Roles in Feeds for Intestinal Health and Growth of Nursery Pigs - Hyunjun Choi; Sung Woo Kim (Animals, 2023)
The objectives of this review are to investigate the quantitative, compositional, and structural differences of β-glucans and the functional effects of β-glucans on the intestinal health and growth of nursery pigs. Banning antibiotic feed supplementation increased the research demand for antibiotic alternatives to maintain the intestinal health and growth of nursery pigs. It has been proposed that β-glucans improve the growth efficiency of nursery pigs through positive impacts on their intestinal health. However, based on their structure and source, their impacts can be extensively different. β-glucans are non-starch polysaccharides found in the cell walls of yeast (Saccharomyces cerevisiae), bacteria, fungi (Basidiomycota), and cereal grains (mainly barley and oats). The total β-glucan content from cereal grains is much greater than that of microbial β-glucans. Cereal β-glucans may interfere with the positive effects of microbial β-glucans on the intestinal health of nursery pigs. Due to their structural differences, cereal β-glucans also cause digesta viscosity, decreasing feed digestion, and decreasing nutrient absorption in the GIT of nursery pigs. Specifically, cereal β-glucans are based on linear glucose molecules linked by β-(1,3)- and β-(1,4)-glycosidic bonds with relatively high water-soluble properties, whereas microbial β-glucans are largely linked with β-(1,3)- and β-(1,6)-glycosidic bonds possessing insoluble properties. From the meta-analysis, the weight gain and feed intake of nursery pigs increased by 7.6% and 5.3%, respectively, through the use of yeast β-glucans (from Saccharomyces cerevisiae), and increased by 11.6% and 6.9%, respectively, through the use of bacterial β-glucans (from Agrobacterium sp.), whereas the use of cereal β-glucans did not show consistent responses. The optimal use of yeast β-glucans (Saccharomyces cerevisiae) was 50 mg/kg in nursery pig diets based on a meta-analysis. Collectively, use of microbial β-glucans can improve the intestinal health of nursery pigs, enhancing immune conditions, whereas the benefits of cereal β-glucans on intestinal health were not consistent.